The art of the brick - Groves, Derham (Acta Structilia, 2004)
To celebrate Australia’s strong tradition of brick architecture, as well as the largely unsung art of bricklaying, Australian architect and curator, Derham Groves, organized two complementary public exhibitions of full-scale brick structures designed by various architects and artists. The results were an intriguing mixture of art and the everyday, as Groves describes in the following article.